Pharmacokinetics, pharmacodynamics, and safety of asundexian in healthy Chinese and Japanese volunteers, and comparison with Caucasian data - Huijun Chen; Kensei Hashizume; Friederike Kanefendt; Christine Brase; Sebastian Schmitz; Tianxing Liu (Wiley, 2024)
Abstract There is an unmet clinical need for effective anticoagulant therapies for the management of thromboembolic diseases that are not associated with a relevant risk of bleeding. Asundexian (BAY 2433334) is an oral, direct, small‐molecule inhibitor of activated factor XI (FXIa). Phase I data from healthy Caucasian male participants indicated predictable pharmacokinetic (PK) and pharmacodynamic (PD) profiles and no clinically relevant bleeding‐related adverse events (AEs). Reported here are data from two phase I, randomized, placebo‐controlled, single‐ and multiple‐dose escalation studies of asundexian conducted in 60 healthy men: 24 Japanese and 36 Chinese. Baseline characteristics were comparable between the treatment groups. All treatment‐emergent AEs were mild, with no serious AEs or AEs of special interest reported. Systemic exposure to asundexian increased dose proportionally after single or multiple dosing, with relatively low accumulation following multiple once‐daily dosing in both Chinese and Japanese volunteers. Asundexian induced dose‐dependent prolongation of activated partial thromboplastin time and inhibition of FXIa activity, with no effects on prothrombin time or FXI concentration in Japanese participants. There were no clinically relevant interethnic differences in PK profile across the Japanese, Chinese, and Caucasian (data from the previous phase I study) participants and no clinically relevant difference in PD response between Japanese and Caucasian participants.